Assessing the Effectiveness of COBIT Implementation in Improving IT Operational Performance in Indonesian Enterprises - Kardiyasa, Komang Agus Putra; Putra, Anak Agung Adi Wiryya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The impact of COBIT implementation on IT operational efficiency, using a mixed- method approach that focuses on quantitative analysis. A total of 387 valid respondents were obtained through stratified random sampling targeting IT professionals from various industry sectors. This study measured improvements in cost reduction, service response time improvement, and security incident reduction. The results indicate that COBIT implementation significantly correlates with an average operational cost reduction of 28.5%, a 34.2% improvement in service response time, and a 41.7% decrease in security incidents. Organizations with a higher COBIT maturity level (Level 4-5) showed better performance compared to Level 2-3. The DSS domain had the highest impact on efficiency (r = 0.847). The developed predictive model explains 74.3% of the variance in operational efficiency. This research offer practical insights for organizations aiming to enhance IT performance through structured governance. The study provides actionable recommendations, including prioritizing DSS processes, conducting maturity assessments, and adopting phased implementation strategies to optimize COBIT adoption.